Impact of Renal Function on Long-Term Clinical Outcomes in Patients With Coronary Chronic Total Occlusions: Results From an Observational Single-Center Cohort Study During the Last 12 Years - Guo, Lei; Ding, Huaiyu; Lv, Haichen; Zhang, Xiaoyan; Zhong, Lei; Wu, Jian; Xu, Jiaying; Zhou, Xuchen; Huang, Rongchong (Frontiers in Cardiovascular Medicine, 2020)
Background: The number of coronary chronic total occlusions (CTO) patient with renal insufficiency is huge and limited data are available on the impact of renal insufficiency on long-term clinical outcomes in CTO patients. We aimed to investigate clinical outcomes of CTO percutaneous coronary intervention (PCI) versus medical therapy (MT) in CTO patients according to baseline renal function. Methods: In the study population of 2497, 1220 patients underwent CTO PCI and 1277 patients received medical therapy. Patients were divided into 4 groups based on renal function: group 1 (estimated glomerular filtration rate [eGFR] ≥ 90 ml/min/1.73m2), group 2 (60 ≤ eGFR < 90 ml/min/1.73 m2), group 3 (30 ≤ eGFR < 60 ml/min/1.73 m2), and group 4 (eGFR <30 ml/min/1.73 m2). Major adverse cardiac events (MACE) was the primary end point. Results: Median follow-up was 2.6 years. With the decline in renal function, MACE (p < 0.001) and cardiac death (p < 0.001) were increased. In group 1 and group 2, MACE occurred less frequently in patients with CTO PCI, as compared to patients in the MT group (15.6% vs. 22.8%, p < 0.001; 15.6% vs. 26.5%, p < 0.001; respectively). However, there was no significantly different in terms of MACE between CTO PCI and MT in group 3 (21.1% vs. 28.7%, p = 0.211) and group 4 (28.6% vs. 50.0%, p = 0.289). MACE was significantly reduced for patients who received successful CTO PCI compared to patients with MT (16.7% vs. 22.8%, p = 0.006; 16.3% vs. 26.5%, p = 0.003; respectively) in group 1 and group 2. eGFR < 30 ml/min/1.73 m2, age, male gender, diabetes mellitus, heart failure, multivessel disease and medical therapy were identified as independent predictors for MACE in patient with CTOs. Conclusions: Renal impairment is associated with MACE in patients with CTOs. For treatment of CTO, compared with medical therapy alone, CTO PCI may reduce the risk of MACE in patients without CKD. However, reduced MACE from CTO PCI among patients with CKD was not observed. Similar beneficial effects were observed in patients without CKD who underwent successful CTO procedures.